Bilateral trade and conflict heterogeneity: The impact of conflict on trade revisited - Katrin Kamin (Kiel Institute for the World Economy (IfW Kiel), 2022)
Although the number of interstate disputes has fallen in the past 30 years, rising geopolitical competition is challenging the foundation of the absence of great power war. Additionally, the number of internal conflicts is surging. At the same time, globalisation has spun a net of global trade connections and has thus created dependencies, making everyone more vulnerable to the repercussions of conflict. In this context, this paper analyses the relationship between trade and conflict from a trade perspective: Using data from UCDP and COMTRADE this paper studies the effects of five different conflict types on international trade flows in the period 1992 - 2011, including interstate and internal conflicts as well as other types of violence.Applying the gravity equation of international trade and the ppml high-dimensional fixed effects estimator, this paper finds that the heterogeneity of conflict types and their distinct characteristics matter for the magnitude and direction of their influence on trade.
Keywords: F14; F51; 330; Gravity; Trade; Conflict